The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1371/journal.pone.0156981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel NLRP12 Nonsense Mutation (Trp408X) in the Extremely Rare Disease FCAS by Exome Sequencing

Abstract: Familial cold autoinflammatory syndrome (FCAS) is an extremely rare autosomal dominant inherited disease. Although there are four genes that have been linked with FCAS, its molecular diagnosis has been challenging in a relatively large proportion of cases. In this study, we aimed to investigate the genetic defect of a recruited FCAS family using exome sequencing followed by in-depth bioinformatics analysis. As a result, a novel heterozygous stop-gain mutation (Trp408X) in NLRP12 was identified in autosomal dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
(27 reference statements)
2
14
0
5
Order By: Relevance
“…Mutations involving NLRP12 / NLRP3 / NLRC4 / PLCG2 genes have been associated with CAPS. However, there are several cases of mutation‐negative patients with the clinical phenotype of CAPS . A case of mutation‐negative FCAS (diagnosed on clinical and cell‐based studies confirming inflammasome dysfunction) has been reported previously, confirming the proposition given above .…”
Section: Discussionsupporting
confidence: 72%
“…Mutations involving NLRP12 / NLRP3 / NLRC4 / PLCG2 genes have been associated with CAPS. However, there are several cases of mutation‐negative patients with the clinical phenotype of CAPS . A case of mutation‐negative FCAS (diagnosed on clinical and cell‐based studies confirming inflammasome dysfunction) has been reported previously, confirming the proposition given above .…”
Section: Discussionsupporting
confidence: 72%
“…The stop-gain mutation (p.W408X) may instead lead to protein dysfunction and, therefore, contribute to disease pathogenesis. This nonsense mutation in NLRP12 is found associated with recurrent fever and skin urticaria due to cold conditions (18). The other variations have been reported as AID-causing mutations in Infevers database (19).…”
mentioning
confidence: 99%
“…У носителей данной мутации при контакте с холодом развивались миалгии и артралгии, тогда как лихорадка и экзантема отсутствовали [24]. В семье, состоявшей из 18 человек, страдавших очень короткими атаками лихорадки и уртикароподобной сыпи продолжительностью не более 12-24 ч, была выявлена му-тация p.Trp408X в гене NLRP12 [25]. Симптомы купирова-лись самостоятельно, без применения медикаментов.…”
unclassified
“…Мутации в гене, приводящие к отсутствию белка или его низкой функциональной актив-ности, вызывают снижение ингибирующей способности белка NLRP12 в отношении пути, связанного с эффектами провоспалительного белка NF-κB. Сниженная ингибирующая способность белка NLRP12 приво-дит к гиперпродукции провоспалительных цитокинов, особенно ИЛ1β, что обусловливает клинические проявления заболевания [24,25]. При проведении функциональных тестов in vitro показано, что некоторые му-тации (p.R284X и 2072+3insT) снижают ингибирующую способность бел-ка NLRP12 [25].…”
unclassified
See 1 more Smart Citation